THE INFLUENCE OF STUDENTS’ UNDERSTANDING OF SENTENCE PATTERN AND VOCABULARY MASTERY ON THEIR READING COMPREHENSION AT THE FIRST YEAR OF STATE VOCATIONAL SENIOR HIGH SCHOOL 1 LOGAS TANAH DARAT KUANTAN SINGINGI REGENCY - Sepri, Sepri (Journal of Education and Teaching, 2021)
The main purpose of this research is to find out the influence of students’ understanding of sentence pattern and vocabulary mastery on their reading comprehension of recount text at State Vocational Senior High Schoo 1 Logas Tanah Darat Kuantan Singingi Regency. This is a correlational research that consists of three variables; two independent variables, namely the students’understanding of sentence pattern and their vocabulary mastery, and one dependent variable which is the students’ reading comprehension of recount text. The research participants consisted of 175 tenth-grade students at the State Vocational Senior High School. The instruments that were used to collect the data are tests. After analysing the collected data by using SPSS, the results showed that the students’ understanding of sentence pattern is at the high level (M = 73.30, SD = 1.59) and their vocabulary mastery is also at the high level (M = 70.97, SD = 1.56). Besides, their reading comprehension of recount text is at the high level too (M = 67.91, SD = 1.66). After analysing the data by using multiple regressions, the finding indicated that there is a significant influence of the students’ understanding of sentence pattern and vocabulary mastery on their reading comprehension of recount text, in which F = 82.14, p=0.000<0.05. Then the percentage of the students’ understanding of sentence pattern and vocabulary mastery is 0.842 (84.20%). Therefore, the alternative hypothesis is accepted and the null hypothesis is rejected. Keywords: Influence, Sentence Pattern, Vocabulary Mastery, Reading  Comprehension